Memfortifikasi Kaidah Agama Dalam Membendung Dampak Globalisasi Melalui Pancasila - Insan Tajali Nur (CV Putra Publisher, 2023)
This paper discussed the effects, impacts and measures to stem the rapid globalization of a region. The progress of globalization affects other sectors in life, such as political, economic, social, legal and cultural fields and the most important is religious values, without realizing this impact eliminates the identity of a nation. Age of children and adolescents is the most span of age with the influence of the effects of globalization both negative impacts and positive impacts. Considering that each religion in Indonesia has provisions and roles in the universal sphere, religion has an important role today which is not only a tool or agent and content of globalization but also a part of the identity of the Indonesian nation. Globalization itself greatly influences the existence of culture, religion, philosophy, politics and law that have been running and vice versa, but religion has a role to be a filter. Therefore, the Indonesian state which has the ideology of Pancasila needs to strengthen Pancasila education, especially the practice of the First and Third Precepts and the importance of actualizing Pancasila with the Integration of Nationalism and Religiousity to the Ruler and Society.